Empirical study: social and financial performance of Islamic rural bank in Indonesia - Utami, Cahyaning Budi; Mubarok, Ahmad Fauzan; Ivantri, Madha Adi; Minah, Zakiyatul; Amalia, Lutfi Nur (Indonesian Journal of Islamic Economics Research, 2024)
Islamic Rural Bank (BPRS) in Indonesia have developed rapidly and reached the lower levels of society. As an islamic institution, BPRS has both financial and social purpose. The effect of social performance on financial performance in BPRS has yet to be widely studied, especially using quantitative data over a long period. This research aims to determine the influence of social performance on financial performance at BPRS in Indonesia. This research uses internal factors (bank characteristics) and external factors (macroeconomic variables) as control variables. Generalized Method of Moments (GMM) parameter was used with Stata software to estimate selected BPRS panel data in the 2012-2021. The result shows that zakat has a positive and significant effect on financial performance at a significance level 0.01. The managerial implication of this study is to encourage Islamic rural banks to pay and report zakat.